Anemia en niños menores de cinco años. ¿Estamos usando el criterio diagnóstico correcto? - Gonzales, Gustavo F. (2019)
Although the prevalence of anemia has decreased in the last decades, global anemia prevalence remains at around 30 % and is estimated to contribute to nearly 9 % of global years lived with disability. An increased appreciation of the multiple interacting causes of anemia to include nutritional, infectious and genetic causes is not reflected in government programs to address anemia which focus only on iron supplementation, which may underlie their limited effectiveness. Additionally, several studies question the validity of the hemoglobin cut-off points used to define anemia, first proposed in 1969 by the WHO, especially those recommended for use in populations at high altitude (HA), as populations at HA generally exhibit higher hemoglobin levels as one of several possible adaptations to living at HA. Use of this criteria may increase 5-6 times the prevalence of anemia, particularly in populations over 3000 meters. In Peruvian populations, anemia is most common in HA and jungle regions, but the etiology is likely to differ due to different dietary, infectious and genetic patterns between these regions. In this review are shown evidences that threshold of hemoglobin to define anemia in children do not agree with the threshold of 11 g/dL of Hb recommended by the World Health Organization. Evidence is also described that suggested correction of hemoglobin by altitude of residence recommended also by the WHO is also unnecessary increasing the prevalence of anemia in high-altitude populations. In conclusion, the Hb threshold of 11 g/dL used to diagnose anemia in children under 60 months of age should be redefined. In addition, as iron deficiency is not the only cause for anemia, other biomarkers should be considered to evaluate the content of body iron, inflammatory contribution, folate, vitamin B12 and vitamin A deficiency. By these means we can accurately diagnosed cause of anemia and give the adequate intervention.